Traditional Market Management Information System in Bima Regency - M. Dermawan Mulyodiputro (LPPM Universitas Qamarul Huda Badaruddin, 2018)
Management information systems are needed in all areas of human life, including in traditional markets that involve many people with various activities. In Bima Regency, there are many traditional markets spread across several sub-districts in Bima Regency. The information system that is used in all traditional markets in Bima Regency is still manual, this causes the market operators to find difficulty in finding the data of traders who have not paid the retribution fee. The problem of managing market levies that is not optimal causes a lack of security for the management of user fees, thus causing PADs that are generated by local governments to be sourced from traditional markets. The research method is done by the waterfall method. The development of traditional market management information systems is carried out using the Java programming language with object-oriented programming methods. The menus produced include: market menu, survey menu, commodity menu, trader menu, retribution menu, and report menu.